Air Displacement Plethysmography: Validation in Overweight and Obese Subjects - Ginde, Samir R; Geliebter, Allan; Rubiano, Frederick; Silva, Analiza M; Wang, Jack; Heshka, Stanley; Heymsfield, Steven B (Obesity (Silver Spring, Md.), 2005)
16.9 years; BMI, 31.5 ± 7.3 kg/m²); 15, 70, and 10subjects were overweight (25 </= BMI < 30 kg/m²), obese (30</= BMI < 40 kg/m²), and severely obese (BMI [>/=] 40kg/m²), respectively. RESULTS: There was a strong correlation between D[subscript b](kilograms per liter) measured by UWW and ADP (r =